Autism Spectrum Disorder and collective catering service: results of the pilot study FOOD-AUT - Conti, Maria Vittoria; Santero, Sara; Breda, Chiara; Basilico, Sara; de Filippo, Giorgia; Luzzi, Alessia; Voto, Luana; Cavagnola, Rebecca; Tomasinelli, Chiara Elena; Cena, Hellas (Frontiers in Nutrition, 2024)
Objective: Individuals with Autism Spectrum Disorder (ASD) often exhibit a low dietary diversity due to food selectivity that leads them to a marked preference for high-energy-density food, exposing them to risk of malnutrition. Despite these aspects, specific recommendations and targeted menus for this population are missing. The pilot study FOOD-AUT addresses this issue by developing canteen menus meeting the nutritional and sensory needs of adults with ASD, aiming to reduce their food selectivity, and consequently improving their health. Methods: The project, funded by Gruppo Pellegrini S.p.A, was conducted at the daycare service of Sacra Famiglia Onlus Foundation, between March-2022 to March-2023. The study was divided into two phases. Observational phase: a comparison was made between the enrolled subjects' nutritional needs and the nutrient content of the administered menus during the daycare service. Then mealtime compliance was assessed using standardized meal evaluation forms, both quantitative and qualitative. Intervention phase: canteen menus targeted to the individuals' nutritional and sensory needs were administered and their acceptability was evaluated. Results: Twenty-two individuals with ASD, aged 19-48, 72.7% males, were enrolled. Overweight and obesity prevalence were 54.5% and 18.2% respectively. The observational phase showed how the most accepted foods had specific sensorial characteristics in line with the scientific literature. Adapting the menus improved food acceptance and reduced food waste.The results highlighted the need for adapted menus and greater attention to the way meals are delivered and consumed to improve nutritional status and therefore health of this population at increased risk of malnutrition.